Utilizing the reaction of degeneration test for individuals with focal paralysis - Holland, Thomas J (Journal of Brachial Plexus and Peripheral Nerve Injury, 2012)
Background and purpose Neuromuscular electrical stimulation (NMES) is a modality sometimes used to help strengthen weak muscles. On occasion, however, the targeted muscles do not respond to the current delivered. No response to electrical stimulation should raise the consideration of unsuspected peripheral nerve damage. Two case studies are presented showing how absence of response was due to unsuspected peripheral neuropathy, which had not been considered in either of the original referral diagnoses.Case descriptions The first individual sustained head trauma and did not respond to NMES to facilitate finger flexor contractions in the left hand. This prompted a reaction of degeneration test (R/D test) which revealed evidence of a median nerve lesion. The second individual presented with right ankle dorsiflexor and evertor paralysis following a right total hip replacement. The R/D test helped rule out a central nervous system lesion by revealing evidence of right peroneal nerve degeneration.Conclusion The case reports show how clinical suspicion followed by simple R/D testing can be used to screen for nerve damage, prompting further electrodiagnostic work up of individuals with profound weakness and or paralysis.
Keywords: Peripheral nerve lesion; Reaction of degeneration test; Electrodiagnosis